The Spillover Effect of the Consumerism Trap: Analyzing Nauru’s Resource Curse Phenomenon to Voluntary Simplicity Prescriptions for Nauruans - Perbawani, Firsty Chintya Laksmi (Journal of International Relations on Energy Affairs, 2021)
The flow of people and goods with the existence of globalization brought a new pattern of life. People tend to change their consumption pattern from fulfilling the basic needs to becoming consumerism; a behavior of buying goods and services that are more concerned with what is desired than what is needed. This phenomenon established a new problem called the consumerism trap; a dilemmatic situation in which we want to dismiss consumerism but the impact it causes is even more detrimental. The upcoming question will be about, is consumerism trap is increasingly escalated with globalization in this contemporary era? The author argues that globalization accelerates the pattern of consumerism. This paper portrays Nauru as the best example to support the author’s argument because it shows that Nauruans are complacent with their wealth of phosphate resources, then become lazy, dependent, and finally adopt a consumerism lifestyle. It made Nauruans trapped in spillover problems, like environmental degradation, obesity, financial flows by build shell banks, etc. To sum up, the era of globalization increasingly giving space for people to be trapped in the consumerism trap; moreover, society does not see the continued implications of consumerism. By analyzing Nauru, we learned how globalization accelerates consumerism and creating spillover effects for the country. At the end, the author gives a prescription to solve this problem by doing voluntary simplicity as the antithesis of consumerism.